2014
DOI: 10.1128/aac.01790-12
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Polymorphisms Associated with Ex Vivo Drug Susceptibility and Clinical Effectiveness of Artemisinin-Based Combination Therapies in Benin

Abstract: h Artemisinin-based combination therapies (ACTs) are the main option to treat malaria, and their efficacy and susceptibility must be closely monitored to avoid resistance. We assessed the association of Plasmodium falciparum polymorphisms and ex vivo drug susceptibility with clinical effectiveness. Patients enrolled in an effectiveness trial comparing artemether-lumefantrine (n ‫؍‬ 96), fixed-dose artesunate-amodiaquine (n ‫؍‬ 96), and sulfadoxine-pyrimethamine (n ‫؍‬ 48) for the treatment of uncomplicated mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
6
24
0
Order By: Relevance
“…Nonetheless, we show that the 86Y mutation was significantly associated with increased susceptibility to MQ (P ϭ 0.00002). These results are in accordance with previous studies in Asia (12,42) and in Benin (43) and are strengthened by field studies demonstrating MQ selection of the N86 allele in recurrent infections after treatment with artesunate plus MQ (44).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Nonetheless, we show that the 86Y mutation was significantly associated with increased susceptibility to MQ (P ϭ 0.00002). These results are in accordance with previous studies in Asia (12,42) and in Benin (43) and are strengthened by field studies demonstrating MQ selection of the N86 allele in recurrent infections after treatment with artesunate plus MQ (44).…”
Section: Discussionsupporting
confidence: 82%
“…These results are in accordance with previous in vitro studies in Asia (45), Kenya (17), and Benin (43). Field studies in east Africa also have shown selection of the 86N allele in recurrent infections after treatment with artemether plus LMF (39,40,46,47), which suggests that 86N is a marker of LMF resistance in vivo.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Third, we Associations of ex vivo drug sensitivity with transporter polymorphisms. We and others have previously shown that polymorphisms in the putative transporters pfcrt and pfmdr1 are associated with altered ex vivo drug sensitivity (7,12,(34)(35)(36)(37)(38). We tested for associations between pfcrt K76T and pfmdr1 N86Y, Y184F, and D1246Y polymorphisms, and the ex vivo drug sensitivities were determined for samples collected in 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%